PENGARUH KEYAKINAN DIRI SISWA SMK TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Reyna Suhartina; Luvy Silviana Zanthy (Journal on Education, 2019)
This study aims to review how much influence students' self-confidence has on mathematical creative thinking skills. The method used in this study is the correlational method and quantitative approach. The population in this study was carried out in one of the vocational schools in Cimahi City and the sample in this study was 29 students of Vocational High School class XI RPL D. The instruments in this study were in the form of tests of mathematical creative thinking skills as many as 5 items of description questions then non-test instruments in the form of self-confidence scale as many as 20 scale positive statements and negative statements. The stage carried out in this study was to fill out the test questions about the ability of mathematical creative thinking and filling in the self-confidence questionnaire of vocational students. The results obtained from this study are that the self-confidence of vocational students does not have an influence on mathematical creative thinking abilities, the value obtained by 0.3% and 99.7% is influenced by other factors than the ability of students.